2018
DOI: 10.1101/486407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dengue and Chikungunya among Febrile Outpatients in Kinshasa, Democratic Republic of Congo: a cross-sectional study

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Although no epidemics have been reported in the country, our study shows an ongoing arboviral activity in the studied population. The prevalence data on CHIKV was in line with seroprevalence studies conducted in other African countries such as Congo Brazzaville and Democratic Republic of Congo in which an estimate of 34.4% and 24.6% respectively had been reported [37,38]. However, it was far higher than that found in Tanzania [39].…”
Section: Discussionsupporting
confidence: 86%
“…Although no epidemics have been reported in the country, our study shows an ongoing arboviral activity in the studied population. The prevalence data on CHIKV was in line with seroprevalence studies conducted in other African countries such as Congo Brazzaville and Democratic Republic of Congo in which an estimate of 34.4% and 24.6% respectively had been reported [37,38]. However, it was far higher than that found in Tanzania [39].…”
Section: Discussionsupporting
confidence: 86%
“…This compel introduction of arboviral testing in the routine laboratory procedures. However absence of dengue infection in our study population and other African settings can possibly be due to lower OSBPL10 expression pro le in Africans which is protective against viral hemorrhagic fever and dengue shock syndrome (22). Transmission occurs mostly during epidemics.…”
Section: Discussionmentioning
confidence: 66%
“…Further investigation of all cases revealed that 11.7% ( 23) had chikungunya virus while none had dengue virus. For the cases of chikungunya, 78.3% (18) were below 5 years of age, 65.2% ( 15) were females, majority were from Kilimanjaro 95.7% ( 22) and Arusha region 4.3% (1). The clinical features were as follows; nausea/vomit 50.0% (98), cough 48.5% (95), convulsion/comma 34.7%( 68), diarrhea 26.0% (51), joint pain 13.3% (26), sore throat 7.1% ( 14), rashes 4.1%(8)chills 2.6% 5 .…”
Section: Resultsmentioning
confidence: 98%
“…Probable chikungunya cases were observed in Cité Verte and Ngaliema during the poorly documented chikungunya outbreak in 2012 [27,30,31,34]. Furthermore, antibodies against CHIKV and DENV were reported in approximately 30% of febrile patients from Selembao and Ngaliema, tested in 2005-2006 [29].…”
Section: Study Sitesmentioning
confidence: 99%